Impaired axonal transport in motor neurons correlates with clinical prion disease. - Vladimir Ermolayev; Toni Cathomen; Julia Merk; Mike Friedrich; Wolfgang Härtig; Gregory S Harms; Michael A Klein; Eckhard Flechsig (PLoS Pathogens, 2009)
Prion diseases are fatal neurodegenerative disorders causing motor dysfunctions, dementia and neuropathological changes such as spongiosis, astroglyosis and neuronal loss. The chain of events leading to the clinical disease and the role of distinct brain areas are still poorly understood. The role of nervous system integrity and axonal properties in prion pathology are still elusive. There is no evidence of both the functional axonal impairments in vivo and their connection with prion disease. We studied the functional axonal impairments in motor neurons at the onset of clinical prion disease using the combination of tracing as a functional assay for axonal transport with immunohistochemistry experiments. Well-established and novel confocal and ultramicroscopy techniques were used to image and quantify labeled neurons. Despite profound differences in the incubation times, 30% to 45% of neurons in the red nucleus of different mouse lines showed axonal transport impairments at the disease onset bilaterally after intracerebral prion inoculation and unilaterally -- after inoculation into the right sciatic nerve. Up to 94% of motor cortex neurons also demonstrated transport defects upon analysis by alternative imaging methods. Our data connect axonal transport impairments with disease symptoms for different prion strains and inoculation routes and establish further insight on the development of prion pathology in vivo. The alterations in localization of the proteins involved in the retrograde axonal transport allow us to propose a mechanism of transport disruption, which involves Rab7-mediated cargo attachment to the dynein-dynactin pathway. These findings suggest novel targets for therapeutic and diagnostic approaches in the early stages of prion disease.